FPGA Based Firewall using Embedded Processor for Vulnarability Packet Detection - Mohamed Yousuf Hasan; Poornima V.P; Sujendran S; Karthikraja D (International Journal of Reconfigurable and Embedded Systems (IJRES), 2014)
This paper describes the design of high performance packet filtering firewall using embedded system. An FPGA (field programmable gate array) platform has been used for implementation and analysing the network firewall. It is capable of accepting real time changes. This network security application has an ability to perform powerful protection against unwanted data packets such as virus attack, spam in e-mails, hackers, worms, spyware unauthorized contents. However the firewalls don’t address the difficulty of unwanted data packets intrusion. The ultimate aim of this work is to create a systematic way of approach for unwanted packets discard in a network system. We use a specially trained algorithms such as Wu-manber algorithms (high performance, multi-pattern matching), bloom filter algorithm (space efficient data structure for testing an element in the set.Our design is mainly based on machine learning and artificial intelligence. This gives a high efficiency, improved performance and high ability of packet detection with less contribution of time in an effective way.